Inovasi Literasi Guru Melalui Pendampingan Penulisan Puisi Berbasis AI - Qur'ani, Hidayah Budi; Kumalasani, Maharani Putri; Ulum, Bahrul; Nuryasin, Mohammad (Universitas Muhammadiyah Mataram, 2026)
Abstract: Technological developments and digitalization require teachers to innovate. Innovation can be realized by having competence in empowering AI. Based on that, this community service activity aims to (1) improve teachers' creative literacy competencies through AI-based poetry writing training and (2) integrate AI technology in literature learning in elementary schools, especially in the creative process of writing poetry. This community service is in partnership with fifth-grade Indonesian language teachers at Muhammadiyah 9 Elementary School, Malang City. This community service uses a training method consisting of five stages of activities, namely socialization, training, technology application, mentoring and evaluation, and sustainability. The results of this community service are (1) an increase in competence in creative literacy aspects, especially in AI-based poetry writing and (2) an increase in the ability to integrate AI in literature learning in elementary schools. The overall community service results were obtained through direct interviews with community service participants.Abstrak: Perkembangan teknologi dan digitalisasi menuntut guru untuk berinovasi. Inovasi dapat direalisasikan dengan memiliki kompetensi dalam memberdayakan AI. Berdasarkan hal itu, kegiatan pengabdian ini bertujuan untuk (1) meningkatkan kompetensi literasi kreatif guru melalui pelatihan penulisan puisi berbasis AI dan (2) mengintegrasikan teknologi AI dalam pembelajaran sastra di sekolah dasar, khususnya dalam proses kreatif menulis puisi. Pengabdian ini bermitra dengan guru bahasa Indonesia kelas V SD Muhammadiyah 9 Kota Malang. Pengabdian ini menggunakan metode pelatihan yang terdiri atas lima tahap kegiatan, yaitu sosialisasi, pelatihan, penerapan teknologi, pendampingan dan evaluasi, serta keberlanjutan. Hasil pengabdian ini berupa (1) adanya peningkatan kompetensi dalam aspek literasi kreatif, khususnya dalam penulisan puisi berbasis AI dan (2) adanya peningkatan kemampuan untuk mengintegrasikan AI dalam pembelajaran sastra di sekolah dasar. Hasil pengabdian secara keseluruhan didapatkan melalui wawancara secara langsung terhadap peserta pengabdian.